A study on the occupational health concerns and safety of library employees of the University of the Philippines Diliman Library System - Cadiz, Nino Mar Angelo R. (2010)
This is a descriptive study of common occupational health and safety illnesses and diseases among the 128 library staff of University of the Philippines Diliman. It aims to investigate the various occupational health and safety illnesses and diseases among the library staff by tasks. It further identifies the causes of such illnesses and diseases as well as the preventive measures that were employed by the library administration and personnel.